Rational Design of Cancer Nanomedicine: Nanoproperty Integration and Synchronization. Issue 14 (24th February 2017) - Sun, Qihang; Zhou, Zhuxian; Qiu, Nasha; Shen, Youqing
Abstract : Current cancer nanomedicines can only mitigate adverse effects but fail to enhance therapeutic efficacies of anticancer drugs. Rational design of next‐generation cancer nanomedicines should aim to enhance their therapeutic efficacies. Taking this into account, this review first analyzes the typical cancer‐drug‐delivery process of an intravenously administered nanomedicine and concludes that the delivery involves a five‐step CAPIR cascade and that high efficiency at every step is critical to guarantee high overall therapeutic efficiency. Further analysis shows that the nanoproperties needed in each step for a nanomedicine to maximize its efficiency are different and even opposing in different steps, particularly what the authors call the PEG, surface‐charge, size and stability dilemmas. To resolve those dilemmas in order to integrate all needed nanoproperties into one nanomedicine, stability, surface and size nanoproperty transitions (3S transitions for short) are proposed and the reported strategies to realize these transitions are comprehensively summarized. Examples of nanomedicines capable of the 3S transitions are discussed, as are future research directions to design high‐performance cancer nanomedicines and their clinical translations. Abstract : Rational design of next‐generation cancer nanomedicines should aim to enhance their therapeutic efficacies. The typical cancer‐drug delivery involves a five‐step CAPIR cascade and that high efficiency at every step is critical to guarantee high overall therapeutic efficiency. Stability, surface, and size nanoproperty transitions (3S transitions for short) are proposed, and the reported strategies to realize these transitions are comprehensively summarized.